“Made in China” : a study of China’s export competitiveness - Quah, Jalean Hui Fen (2015)
China’s export competitiveness is beyond compare. Exactly how China rose to become a worldwide recognisable brand is an interesting question as China’s success story can surface the key ingredients to increase export competitiveness. This leads to suggestions for China’s export competitors towards the fine-tuning of their export policies. To do so, this paper adopts a quantitative study on eleven of China’s top export commodities to analyse the factors that boost China’s export demands. Upon drawing out the demand pattern of each commodity, the GDP of United States is deemed as the most important factor behind the driving of China’s success. As an enhancement, further theoretical reasons for China export competitiveness are discussed to complement the quantitative study. In order to assess the significance of the result’s implications, a case study is conducted with India as the reference country. The case study concluded that India might not be able to follow China’s footsteps and replicate her success story through the application of the quantitative results and the theoretical reasoning. Lastly, the question of an expiry date for China’s export competitiveness is being raised and a brief discussion of the substantiality of China’s export competitiveness is provided.